2019
DOI: 10.1017/s0007114519000679
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of differentiation 36 gene polymorphism (rs1761667) is associated with dietary MUFA intake and hypertension in a Japanese population

Abstract: Cluster of differentiation 36 (CD36) is a membrane receptor expressed on a wide variety of human cells. CD36 polymorphisms are reportedly associated with oral fat perception, dietary intake and metabolic disorders. The present study examined associations of two CD36 polymorphisms (rs1761667 and rs1527483) and dietary fat intake, and metabolic phenotypes in a Japanese population. This cross-sectional study was conducted based on clinical information collected from health check-ups in Japan (n 495). Dietary nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 53 publications
(70 reference statements)
0
17
0
Order By: Relevance
“…General characteristics of the 18 eligible studies are provided in Table 1 . Six studies were from Asia 7 , 15 , 19 , 25 – 27 , five from African 8 , 11 , 20 22 , and six from Europe 13 , 14 , 17 , 18 , 23 , 24 ,and one study was from the USA/Italy 16 . The majority of eligible studies included both sexes and only two 20 , 27 and one 17 studies were performed on women and men, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…General characteristics of the 18 eligible studies are provided in Table 1 . Six studies were from Asia 7 , 15 , 19 , 25 – 27 , five from African 8 , 11 , 20 22 , and six from Europe 13 , 14 , 17 , 18 , 23 , 24 ,and one study was from the USA/Italy 16 . The majority of eligible studies included both sexes and only two 20 , 27 and one 17 studies were performed on women and men, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The participants were aged 18–75.73 years and the mean body mass index was ranged from 21.66 to 34.60 kg/m 2 . Seven studies were conducted on healthy individuals 16 18 , 20 , 21 , 23 , 27 , three studies targeted patients with heart diseases 7 , 8 , 19 , one study included individuals with T2DM 25 , metabolic syndrome 11 , and the six remaining studies included adults with other health status 13 – 15 , 22 , 24 , 26 . In the majority of studies, genotype distributions were in HWE 7 , 11 , 13 , 15 , 16 , 21 , 22 , 24 27 .…”
Section: Resultsmentioning
confidence: 99%
“…In studies of Tunisian (13) and Algerian individuals (32) , individuals with the AA mutant genotype showed lower intensity of fat perception and a preference for added fat and oil; hence, these individuals had higher fat intake than individuals with the genotype with the G allele (2) . Additionally, studies have clearly suggested that the genetic variant was associated with clinical outcomes, including lower rates of hypertension, coronary artery disease and liver fibrosis (33)(34)(35) . The association between the variation in CD36 and fat sensing may be explained as follows.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the CD36 gene polymorphism, which causes a decrease of CD36 protein expression, is directly associated with 1 https://www.ncbi.nlm.nih.gov/gene/948 the capability to detect dietary FA and the preference for fatrich diet (Keller et al, 2012;Pepino et al, 2012;Fujii et al, 2019;Bajit et al, 2020). Inhibition of CD36 on ventromedial hypothalamus (VMH) neurons leads to insensitivity of neurons to FA loadings, which may cause more food intake and body weight gain, development of fatty liver and insulin resistance in rats, suggesting CD36 is a critical molecular in both neuronal FA sensing and the regulation of metabolic homeostasis (Le Foll et al, 2015).…”
Section: Cd36 Regulates Dietary Fat Intakementioning
confidence: 99%